2000
DOI: 10.1088/0022-3727/33/11/313
|View full text |Cite
|
Sign up to set email alerts
|

The numerical modelling of Joule heating effects in thoriated tungsten cathodes of high-current plasma arcs

Abstract: The influence of the Joule heating on the performance of thoriated tungsten cathodes working at current densities of 10 3 -10 4 A cm −2 is investigated. The variation of the degree of coverage of the cathode surface by thorium atoms is considered, together with the heat conduction and the diffusion of thorium in the cathode bulk. The nonlinear system of equations governing these processes is solved numerically and the time evolution of the spot temperature is obtained. The effects of different working conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Temperature gradients of the order of 10 4 K/µm are reported in this region [22]. The problem is further complicated by the existence of protrusions at the microscopic scale, both originally present and induced by erosion; this in turn depends on tip shape, angle [23] and material [24] and on the presence of contaminants, e.g. oxygen, hydrocarbons and water vapours in the surrounding gas.…”
Section: Tig Arc Structure and Propertiesmentioning
confidence: 99%
“…Temperature gradients of the order of 10 4 K/µm are reported in this region [22]. The problem is further complicated by the existence of protrusions at the microscopic scale, both originally present and induced by erosion; this in turn depends on tip shape, angle [23] and material [24] and on the presence of contaminants, e.g. oxygen, hydrocarbons and water vapours in the surrounding gas.…”
Section: Tig Arc Structure and Propertiesmentioning
confidence: 99%
“…Several studies [1][2][3][4][5] have been conducted by experimental observation and numerical simulation in order to investigate the electrode consumption. Sadek et al 1) observed the electrodes tip microstructure after a TIG welding operation.…”
Section: Introductionmentioning
confidence: 99%
“…Casado et al 3) developed a one dimensional model considering a diffusion of additives on the electrode axis and investigated the effect of Joule heating on the electrode lifetime under high current conditions. Nishiyama et al 4) investigated the effects of the electrode shape and the current value on the electrode lifetime by the computational model considering not only Joule heating but also a heat conduction from the arc plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The thermodynamic and transport properties of argon, tungsten and stainless steel are given as a function of temperature. 10,[15][16][17][18][19][20][21] The viscosity in the solid-liquid mushy zone is as a function of liquid fraction. Figures 2(a) and 2(b) show the effect of sulfur content on the temperature fields of arc and molten pool.…”
Section: Governing Equationsmentioning
confidence: 99%